2021
DOI: 10.3390/ijerph18083987
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Autonomy Support on Leisure-Time Physical Activity via Cognitive Appraisals and Achievement Emotions: A Mediation Analysis Based on the Control-Value Theory

Abstract: Analyzing students’ emotional experience in physical education (PE) is of crucial importance as it may fill an important gap in research examining the role of PE for students’ leisure-time physical activity (PA). Based on the control-value theory of achievement emotions, the purpose of this study was to test the assumption that multi-dimensional autonomy support of the PE teacher may affect students’ leisure-time PA via their appraisals of control and value and achievement emotions experienced in PE. Variance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 105 publications
(187 reference statements)
2
40
0
1
Order By: Relevance
“…Additionally, we showed that autonomy support is related to the satisfaction of autonomy, which is associated with satisfaction of competence and belonging as well [ 15 , 24 , 39 ]. In conclusion, and in line with previous findings, autonomy support is positively related to the satisfaction of the three basic psychological needs, which in turn predicts enjoyment in PE [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, we showed that autonomy support is related to the satisfaction of autonomy, which is associated with satisfaction of competence and belonging as well [ 15 , 24 , 39 ]. In conclusion, and in line with previous findings, autonomy support is positively related to the satisfaction of the three basic psychological needs, which in turn predicts enjoyment in PE [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the absence of a standardized German questionnaire to assess teacher autonomy support in PE, when collecting the present data, this study is limited to teacher self-reported autonomy support. Future studies could use the lately validated German Multi-Dimensional Perceived Autonomy Support Scale for Physical Education [ 41 ], as shown recently [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, there were 15 items with five items in each subscale ranging from 1 (strongly disagree) to 7 (strongly agree). Previous studies have supported the validity and reliability of this instrument [5,[19][20][21][22][23][24][25].…”
Section: Weekmentioning
confidence: 81%
“…The teaching strategy based on the development of student autonomy (11–18 years, with a low educational level) in Germany and the generation of positive emotions during physical education lessons can favorably influence leisure physical activities throughout life, with beneficial effects on health [ 16 ]. Physical education teachers, along with the models offered by parents have a major and significant role in supporting leisure and relaxation activities for teenagers.…”
Section: Introductionmentioning
confidence: 99%